(3GdQYGjI dJLhjO GdbQGAI hJMbjb daX GdJdGhIs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s
(3ChdgG (B:s
(3bGd CHheMeO ecj Hf CHj WGdH Hf eMeO QVj Gddg Yfg ELGRI HNW jOg bGd Cbhd GdMeO ddg GdoefYe HBdGFg GdoeJaVd HfYeGFg s
(3BNQgG (B:s
(3aGYQa Pdc hGYQa GdaQb Hjf gPg GdJQGLe Hjf dc GdeYGfj Ef TGA Gddg JYGdi Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3fSNI Chdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B908s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs